INSTALASI SISTEM PEMANTAUAN KUALITAS AIR ONLINE BERBASIS GSM DI SUNGAI CILIWUNG SEGMEN ISTIQLAL - Wahjono, Heru Dwi; Setiaji, Galih (Jurnal Air Indonesia, 2015)
Ciliwung River is one of the rivers that pass through the administrative area of Jakarta. Ciliwung river has been categorized as a heavy polluted river. The water quality monitoring needs to be installed to control river pollution. The Water quality monitoring should be performed at any time continuously. For that reason, The trial water quality monitoring that placed in the area of Ciliwung part Istiqlal Mosque has been installed. The installed system that based on GSM network is an online and realtime water quality monitoring. In this paper discusses the process of installation, monitoring results, modification of protective structure and the problems were encountered. From this activity bring out some conclusions about: shape of suitable protective building, sensor calibration period, the obstacles encountered, system reliability, and efforts to improve system performance. Keywords: Protective building, calibration period, monitoring result, water quality, realtime.